PROBLEM BASED LEARNING (PBL) MODEL ON STUDENTS' LEARNING OUTCOMES IN HYDROCARBON MATERIALS - Tara Bunga Noviantika (Jurnal Pembelajaran Sains, 2022)
To improve student learning outcomes requires a learning model that is consistent with the problem-based learning model. This model requires the active participation of each student in solving problems through discussion in order to create an exchange of ideas between students. The results of the review of learning based on problem based learning methods, through this learning model obtained good responses from students. This proves that the problem-based learning model has a positive effect on students. The method used is based on a review of 29 journal articles as secondary data sources and 3 relevant journal articles as primary literature with a bibliographic approach using VOSviewer software. Based on the 29 articles studied, the problem-based learning model improves student learning outcomes on hydrocarbons by an average of 67.65%.